Kebijakan Open Data Penelitian dalam Membangun Komunikasi Ilmiah di Perpustakaan Lembaga Riset - Tupan Tupan Tupan (Institut Agama Islam Negeri (IAIN) Curup, 2021)
A study was conducted on the role of research institute libraries in supporting open data research policies to improve scientific communication. The study aims to determine the role of libraries in open data research policies to improve scientific communication, and determine the role of libraries in relation to the open data research movement in building scientific communication. The research was conducted using the narrative review method, which is research that is carried out looking for articles related to the study of the role of research institutes libraries in open data research policies to improve scientific communication. namely data management plans and research data sharing processes, ensuring the data can be accessed, storing data in repositories and ensuring data can be accessed within a certain period of time. Libraries are the pioneers of the open data research movement by providing consultancy services for data analysis, research data mining, data curation services, data analysis and visualization, and saving research data over a long period of time. The main support provided by the library in building scientific communication is to create meta data and store data in repositories. Provide training in the management and storage of research data for researchers with the aim that the resulting research data can be used and disseminated for further research